Solvent-induced crystallization and phase-transition phenomena in syndiotactic polystyrene and its relatives - Wang, Hai; Men, Yongfeng; Tashiro, Kohji (Frontiers in Soft Matter, 2022)
The studies of time-dependent structural changes in the solvent-induced crystallization and phase transition phenomena have been reviewed by focusing mainly on syndiotactic polystyrene (SPS) and its relatives having the functional groups on the phenyl rings. The time-resolved measurement of X-ray diffraction and vibrational spectra has revealed the structural evolution process in the solvent-induced crystallization of SPS, which depends on the type (polarity, bulkiness, etc.) of the solvent molecules. The heating of the SPS-solvent complexes causes the complicated phase transitions from the delta form (complex) to the gamma form and to the alpha (or beta) form. The introduction of such a polar functional group as OCH3 or halogen units on the phenyl rings enhances the interactions between the SPS and the solvent, the strength of which depends on the substitution position of the OCH3 units on the phenyl ring. For example, the ortho- or para-substitution dissolves the sample quite easily at room temperature, while the meta-substitution makes it possible to create the solvent complexes. The discussion has been made for the structural relation before and after the formation of the solvent-complexes.